Elevated glutaric acid levels in Dhtkd1-/Gcdh- double knockout mice challenge our current understanding of lysine metabolism - Biagosch, Caroline; Kölker, Stefan; Sauer, Sven (Biochimica et biophysica acta. Molecular basis of disease, 2017)
Glutaric aciduria type I (GA-I) is a rare organic aciduria caused by the autosomal recessive inherited deficiency of glutaryl-CoA dehydrogenase (GCDH). GCDH deficiency leads to disruption of l-lysine degradation with characteristic accumulation of glutarylcarnitine and neurotoxic glutaric acid (GA), glutaryl-CoA, 3-hydroxyglutaric acid (3-OHGA). DHTKD1 acts upstream of GCDH, and its deficiency leads to none or often mild clinical phenotype in humans, 2-aminoadipic 2-oxoadipic aciduria. We hypothesized that inhibition of DHTKD1 may prevent the accumulation of neurotoxic dicarboxylic metabolites suggesting DHTKD1 inhibition as a possible treatment strategy for GA-I. In order to validate this hypothesis we took advantage of an existing GA-I (Gcdh−/−) mouse model and established a Dhtkd1 deficient mouse model. Both models reproduced the biochemical and clinical phenotype observed in patients. Under challenging conditions of a high lysine diet, only Gcdh−/− mice but not Dhtkd1−/− mice developed clinical symptoms such as lethargic behaviour and weight loss. However, the genetic Dhtkd1 inhibition in Dhtkd1−/−/Gcdh−/− mice could not rescue the GA-I phenotype. Biochemical results confirm this finding with double knockout mice showing similar metabolite accumulations as Gcdh−/− mice with high GA in brain and liver. This suggests that DHTKD1 inhibition alone is not sufficient to treat GA-I, but instead a more complex strategy is needed. Our data highlights the many unresolved questions within the l-lysine degradation pathway and provides evidence for a so far unknown mechanism leading to glutaryl-CoA.
Available online 22 May 2017
Gesehen am 21.06.2018